Analysis of Teacher Response to Problem Based Learning Model and Scaffolding Model in Science Subjects - M. Dwi Wiwik Ernawati; Haryanto Haryanto; Harizon Harizon; Yusnidar Yusnidar; Nikma Nur Qoidah; Mitha Udhiyah (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to evaluate teachers' responses to two learning models, namely problem-based learning and scaffolding, in the context of science subjects at Junior High School Negeri Satu Atap Pematang Jering. Methodology: The methodology used was descriptive quantitative research with a population of teachers in the school. The research sample consisted of 16 teachers selected by purposive sampling. Data were analyzed using descriptive statistics. Main Findings: The main finding of this study shows that most teachers (75%) in Junior High School Negeri Satu Atap Pematang Jering responded positively to the use of problem-based learning and scaffolding models in science learning. These results indicate that both learning models effectively improve the quality of teaching and students' understanding of science materials. Novelty/Originality of this study: The novelty of this research lies in its specific focus on analyzing teachers' responses to problem-based learning and scaffolding models. This research contributes to the existing literature in this field by providing a deeper understanding of how these two learning models can be applied in science learning in secondary schools. The results of this study can serve as a guideline for teachers and schools in selecting and implementing effective learning strategies to improve teacher competence and student learning outcomes in science subjects.